Sistema de energia elétrica portátil usando painel fotovoltaico para aplicação em notebooks - Castelo Branco, Paulo de Tarso Vilarinho (2011)
This study proposes the development of a portable power supply to feed notebook computers and other electronic equipment using photovoltaic energy. The complete system is composed by two polycrystalline photovoltaic modules of 54W in parallel, a classic boost converter that allows to work the photovoltaic modules in the maximum power point (MPP) and to charge two lead-acid valve regulated batteries (VRLA Valve-Regulated Lead Acid) of 40Ah associates in series to form a bus of 24Vcc, and a boost-flyback converter that has as function to raise the battery bank voltage of 24Vcc to output voltage of 250Vcc. The boost converter uses the algorithm perturb and observe (P&O) to track the maximum power point of the photovoltaic modules. On the other hand, in the boost-flyback converter operates in continuous conduction mode (CCM) using peak current mode control technique to regulate the output voltage. To verify the feasibility of the two stage power supply, was developed a prototype with first stage of 120W output power, and the second stage of 200W output power.